2021
DOI: 10.1038/s41398-021-01705-z
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse clinical outcomes in people at clinical high-risk for psychosis related to altered interactions between hippocampal activity and glutamatergic function

Abstract: Preclinical rodent models suggest that psychosis involves alterations in the activity and glutamatergic function in the hippocampus, driving dopamine activity through projections to the striatum. The extent to which this model applies to the onset of psychosis in clinical subjects is unclear. We assessed whether interactions between hippocampal glutamatergic function and activity/striatal connectivity are associated with adverse clinical outcomes in people at clinical high-risk (CHR) for psychosis. We measured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(87 reference statements)
1
4
1
Order By: Relevance
“…Our findings are in line with both pre-clinical and clinical studies which have shown that NMDAR blockade induced by ketamine can increase striatal activity (Breier et al, 1998; Kokkinou et al, 2017), and other evidence for altered hippocampal-basal ganglia relationships in patients with FEP (Schwarz et al, 2022) and individuals at clinically high risk of psychosis (Allen et al, 2021; Modinos et al, 2020). NMDAR blockade can also increase striatal dopamine; however, we were unable to measure dopamine levels in this study (Kegeles et al, 2000; Kokkinou et al, 2017; Vollenweider et al, 2000).…”
Section: Interpretation and Implications For The Pathophysiology Of P...supporting
confidence: 90%
“…Our findings are in line with both pre-clinical and clinical studies which have shown that NMDAR blockade induced by ketamine can increase striatal activity (Breier et al, 1998; Kokkinou et al, 2017), and other evidence for altered hippocampal-basal ganglia relationships in patients with FEP (Schwarz et al, 2022) and individuals at clinically high risk of psychosis (Allen et al, 2021; Modinos et al, 2020). NMDAR blockade can also increase striatal dopamine; however, we were unable to measure dopamine levels in this study (Kegeles et al, 2000; Kokkinou et al, 2017; Vollenweider et al, 2000).…”
Section: Interpretation and Implications For The Pathophysiology Of P...supporting
confidence: 90%
“…44[preprint] The present findings therefore extend our prior work to collectively suggest that (a) hippocampal glutamate is lower, (b) CBF in (clusters spanning) the striatum is greater, and (c) that the relationship between hippocampal glutamate and striatal-insular perfusion is abnormal in CHR patients relative to controls. While previous work has found CHR-associated dysfunction in the relationship between prefrontal GABA and hippocampal blood flow, 22 and between hippocampal glutamatergic metabolites and (i) striatal dopamine, 53 (ii) hippocampal activation (by clinical outcomes), 64 and (iii) hippocampal-striatal connectivity, 64 the current study is the first to demonstrate an aberrant relationship between hippocampal glutamate and striatal blood flow in these patients. Given that hippocampal glutamatergic dysfunction is thought to drive hyperperfusion in the hippocampal-midbrain-striatal circuit, our results provide new empirical evidence of a potential link between these two pathophysiological features in CHR patients, which have so far only been reported in isolation.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies suggested that abnormal functioning and anatomy of the hippocampus may constitute one of the earliest signs of psychosis ( Lieberman et al, 2018 ). Specifically, it has been proposed that dysregulated neurotransmission of glutamatergic circuitry may lead to excitotoxic effects ( Lisman et al, 2008 ) and abnormal hippocampal activation ( Allen et al, 2015 , Allen et al, 2021 , Modinos et al, 2020a , Modinos et al, 2020b ), resulting in volumetric reductions ( Provenzano et al, 2020 ). Moreover, these changes may in turn drive functional and structural abnormalities in dopaminergic neurotransmission ( Modinos et al, 2021 , Stone et al, 2010 ), indicating that the hippocampus could play a key role in the pathophysiology of ScZ by triggering a cascade of events leading to widespread cortical and subcortical circuit changes.…”
Section: Introductionmentioning
confidence: 99%